2015
DOI: 10.1371/journal.pone.0118000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genes Suppressing Interferon Effects in Peripheral Blood Mononuclear Cells during Triple Antiviral Therapy for Chronic Hepatitis C

Abstract: The levels of expression of interferon-stimulated genes (ISGs) in liver are associated with response to treatment with pegylated interferon (PEG-IFN) plus ribavirin (RBV). However, associations between the responses of ISGs to IFN-based therapy and treatment efficacy or interleukin-28B (IL28B) genotype have not yet been determined. Therefore, we investigated the early responses of ISGs and interferon-lambdas (IFN-λs) in peripheral blood mononuclear cells (PBMCs) during PEG-IFN/RBV plus NS3/4 protease inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…17,20,21 These results are consistent with our initial finding that SOCS1 expression is upregulated in SVR patients compared with non-SVR patients based on a multiplex RT-PCR analysis. However, SOCS-1 expression did not differ between SVR and non-SVR patients in the large sample of 100 patients.…”
Section: Discussionsupporting
confidence: 89%
“…17,20,21 These results are consistent with our initial finding that SOCS1 expression is upregulated in SVR patients compared with non-SVR patients based on a multiplex RT-PCR analysis. However, SOCS-1 expression did not differ between SVR and non-SVR patients in the large sample of 100 patients.…”
Section: Discussionsupporting
confidence: 89%
“…This significant relationship was verified using a univariate regression model for IL28B genotypes on colonic T reg cells. A recent report suggested that the TT genotype is associated with an increase in IL28B induction upon IFN stimulation and lower levels of several mRNAs of genes [43]. Some of those genes, such as SOCS1, SOCS3, and IRF1, are associated with T reg induction and maintenance [4446].…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent studies, the mRNA levels of the following ISGs were quantified by real‐time PCR in 45 of 49 patients: ISG15 ubiquitin‐like modifier ( ISG15 ), ubiquitin specific peptidase 18 ( USP18 ), MX dynamin‐like GTPase 1 ( MX1 ), and retinoic acid‐inducible gene 1 ( RIG ‐ I , encoded by DDX58), ubiquitin ligase ring‐finger protein 125 ( RNF125 ), suppressor of cytokine signaling 1 ( SOCS1 ), suppressor of cytokine signaling 3 ( SOCS3 ), and ring finger protein 11 ( RNF11 ). The specific primers and probes for ISG15 , MX1 , RIG‐I , SOCS1 , SOCS3 , RNF125 , and the specific primers for USP18 were described in the previous reports, and the specific primers and probes for RNF11 were obtained from Applied Biosystems (Carlsbad, CA) as TaqMan Gene Expression Assays (RNF11: Hs00702517_s1). Amplification and detection were performed using an ABI PRISM 7900HT Fast Real‐Time PCR System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%